2015
DOI: 10.1007/s10585-015-9756-8
|View full text |Cite
|
Sign up to set email alerts
|

Tip60 regulates MT1-MMP transcription and invasion of glioblastoma cells through NF-κB pathway

Abstract: A histone acetyltransferase Tat-interacting protein 60 kDa (Tip60) regulates the DNA damage response by acetylating histone and remodeling chromatin. In addition to histone acetyltransferase activity, Tip60 is known to regulate a variety of cellular functions, including gene expression, DNA damage response, cell migration and apoptosis. Lower expression of Tip60 is observed in lymphomas, melanomas, breast, colon, and lung cancer. It is widely accepted that Tip60 functions as a tumor suppressor. However, a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In addition, NFKBIA is an NFκB inhibitor which inhibits the activity of dimeric NF-kappa-B/REL complexes 62 , suggesting a possible mechanism by which H4K12ac modulates MCP2/CCL8 expression. To further analyzed the signaling mechanisms depicted in the in silico analysis, it may be worth directly targeting H4K12ac with siRNA or CRISPR Cas9 techniques to block TIP60 histone acetyl transferase as previously described 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NFKBIA is an NFκB inhibitor which inhibits the activity of dimeric NF-kappa-B/REL complexes 62 , suggesting a possible mechanism by which H4K12ac modulates MCP2/CCL8 expression. To further analyzed the signaling mechanisms depicted in the in silico analysis, it may be worth directly targeting H4K12ac with siRNA or CRISPR Cas9 techniques to block TIP60 histone acetyl transferase as previously described 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of MMPs and TIMPs for tumor progression has been demonstrated in different types of primary and metastatic brain tumors. The expression of a variety of MMPs, including MMP‐2 (Komatsu et al, ), MMP‐3 (Bodey et al, ), MMP‐9 (Nordqvist et al, ; Komatsu et al, ), MMP‐10 (Bodey et al, ), MMP‐13 (Guan et al, ), and MMP‐14 (Takino et al, ), was shown to be associated with a more aggressive behavior in primary brain tumors such as glioblastoma, astrocytoma, and meningioma. Similarly, different MMPs including MMP‐1 (Wu et al, ) and MMP‐2 (Rojiani et al, ) as well as TIMPs such as TIMP‐1(Rojiani et al, ) were overexpressed in brain metastases from lung and breast cancer.…”
Section: Diagnosis and Prognosis Of Cancers By Mmpsmentioning
confidence: 99%
“…Tip60 has been shown to remodel chromatin in several diseases, including several cancers such as lymphoma, melanoma, breast, colon, and lung cancer [28]. Many studies have shown that Tip60 may function as a tumor suppressor [29,30]. Hu et al reported that during the blastocyst stage of development, lack of Tip60 promoted embryo lethality, showing that Tip60 is an essential gene [31].…”
Section: Tip60 Attenuated the Proliferation And Metastasis Of Cca Celmentioning
confidence: 99%